Real-world monitoring of direct oral anticoagulants in clinic and hospitalization settings. (14th October 2017) - Takatsuki, Seiji; Kimura, Takehiro; Sugimoto, Kazutaka; Misaki, Sadaya; Nakajima, Kazuaki; Kashimura, Shin; Kunitomi, Akira; Katsumata, Yoshinori; Nishiyama, Takahiko; Nishiyama, Nobuhiro; Aizawa, Yoshiyasu; Fukuda, Keiichi
Background: The monitoring of the effects of direct oral anticoagulants may be beneficial during emergencies and adverse events. We aimed to explore direct oral anticoagulant monitoring in "real-world" settings, in which monitoring methods are limited and loading time can be estimated based on only patient reports. Methods: In 164 patients, plasma anti-Xa activity was assessed using a STA ® -Liquid Anti-Xa reagent (Diagnostica Stago, Asnieres, France), and prothrombin time was measured using HemosIL ® RecombiPlasTin 2G (Instrumentation Laboratory, Bedford, MA, USA). The loading time was calculated according to the previous dosing time reported by the patient. In the clinic setting, rivaroxaban and apixaban were administered to 103 patients with atrial fibrillation and a blood sample was tested once during a clinic visit. In the hospitalization setting, edoxaban was administered to 61 patients undergoing arthroplasty for prophylaxis of a venous thrombosis and blood samples were tested 3 and 18 h after the last intake. Results: Plasma Xa activity in the clinical setting ranged widely (rivaroxaban: 1.1–424.4 ng/mL, apixaban: 15.4–469.2 ng/mL) during the 11.7 ± 7.0 h following the previous dose. The values varied over a wide range (up to a factor of 2) at the same loading time, especially around the peak period. The plasma anti-Xa activity of rivaroxaban and apixaban showed linear correlations with prothrombin time (R 2  = 0.828 and 0.717, respectively). Edoxaban administration prolonged the prothrombin time by only 1.6 ± 1.1 s from the trough to the peak, to a degree that was negatively correlated with age, but not with plasma creatinine level, creatinine clearance, or body mass index. Conclusion: In real-world settings, plasma anti-Xa monitoring should be interpreted considering the wide variations in data, reflecting the variability in patient-reported loading time and interpatient variability.